Directing Therapy in Pulmonary Arterial Hypertension Using a Target 6 Min Walk Distance - Nancy Rose Porhownik; Renelle Myers; Zoheir Bshouty (Canadian Respiratory Journal)
BACKGROUND: The most effective approaches to escalating advanced therapies in pulmonary arterial hypertension (PAH) are controversial.